Gestión del conocimiento en instituciones de educación superior: caracterización desde una reflexión teórica (2020)
Knowledge management has become a topic of interest for academics and professionals, who recognize its positive impact on the performance of all kinds of organizations, including Higher Education Institutions, however, these present conditions individuals to be considered. For this reason, this article aims to characterize knowledge management in these institutions based on theoretical reflection. The study consists of a bibliographic review of qualitative design, applying the technique of content analysis and interpretation to scientific documents, found in various databases. The results reveal that knowledge management is a process that acquires great relevance for Higher Education Institutions in their effort to successfully develop their substantive functions, however, there are some difficulties that limit their implementation process. To help overcome these challenges, a knowledge management model is proposed consisting of 4 phases: identification, creation, distribution and measurement; adequately adapted to the operation of these organizations. It is concluded that knowledge management is a pending task for them, but the proposed model can be a starting point to achieve significant results.